2016
DOI: 10.1002/jctb.4933
|View full text |Cite
|
Sign up to set email alerts
|

A Streptomyces lividans SipY deficient strain as a host for protein production: standardization of operational alternatives for model proteins

Abstract: BACKGROUND: Extracellular protein production by Gram-positive bacteria, such as Streptomyces, may be complementary to current established protein production processes. The performance of a Streptomyces lividans mutant strain, deficient in the major signal peptidase (SipY) is investigated for the production of proteins secreted via the secondary Tat pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Using these less-constrained models, we could monitor the uptake and excretion rates of numerous metabolites whose exchange could not be considered in previous simulations (see Additional file 5 , MTF and FVA results for iJV1220). The results agree with observations from growth in minimal medium: besides numerous ions not considered in previous models, the model identified amino acids as the preferred nutrients, in agreement with experimental observations (when grown with casamino acids, amino acids are the preferred carbon sources, and as they start to diminish, the cells start using other carbon sources [ 19 , 22 , 43 ]). Overall, the computed MTF fluxes and their respective FVA limits were remarkably similar irrespective of whether they were computed with extensive experimental constraints, with relaxed or even with no constrains at all (other than biomass and minimal secreted protein production) (See Additional file 5 , MTF and FVA results for iJV1220) and agreed with experimentally observed exchange rates, which were within the predicted FVA limits.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Using these less-constrained models, we could monitor the uptake and excretion rates of numerous metabolites whose exchange could not be considered in previous simulations (see Additional file 5 , MTF and FVA results for iJV1220). The results agree with observations from growth in minimal medium: besides numerous ions not considered in previous models, the model identified amino acids as the preferred nutrients, in agreement with experimental observations (when grown with casamino acids, amino acids are the preferred carbon sources, and as they start to diminish, the cells start using other carbon sources [ 19 , 22 , 43 ]). Overall, the computed MTF fluxes and their respective FVA limits were remarkably similar irrespective of whether they were computed with extensive experimental constraints, with relaxed or even with no constrains at all (other than biomass and minimal secreted protein production) (See Additional file 5 , MTF and FVA results for iJV1220) and agreed with experimentally observed exchange rates, which were within the predicted FVA limits.…”
Section: Resultssupporting
confidence: 89%
“…The fluxes computed with the more complete model, iJV1220 show statistically significant changes related to cell envelope, cofactor and nucleotide biosynthesis similarly to iJV710, with differences that can be ascribed to the inclusion of previously unconsidered relevant routes. Being more comprehensive, iJV1220 provides additional details and reproduces better the known experimental behaviour [ 11 , 19 , 22 , 26 , 43 ]. The iJV1220 model displayed a better predictive behaviour, reproducing microarray expression data [ 19 ] and experimental observations of metabolite exchange rates when most constraints on exchange flux limits were relaxed or removed.…”
Section: Discussionmentioning
confidence: 99%
“…Use of L-alanine resulted in a corresponding reduction in NH 4 + needs, which automatically started being excreted. The observed shoulder in growth rate matched a less-defined region (identified by a larger dispersion) in published growth curves [27, 28].…”
Section: Resultssupporting
confidence: 62%
“…We now proceed to show the use of Adaptive DFBA to explore the metabolism of systems with limited knowledge: first, we analyse S. lividans TK21 grown in a complex medium (NMMP complemented with mannitol and casamino acids), over-expressing secretory proteins cloned in the multi-copy plasmid pIJ486 and secreting them through the minor Tat or the major Sec secretion routes, using model proteins that have been shown to display secretion patterns clearly dissociated from growth [28, 29]. Previous studies have shown that the strains of S. lividans TK21 behave similar to those of S. lividans TK24, when grown on similar media [28, 29], and that the metabolic model should be (to the extent known) transferable between them [6].…”
Section: Resultsmentioning
confidence: 99%
“…Heterologous protein yields obtained in S. lividans are often low or inconsistent, driving the research for uncovering production bottlenecks and applying improvement strategies [1, 4]. Screening for alternative promoters and signal peptides [5], codon optimization [6], and optimization of operational conditions [7] have been applied as strategies—with varying success—for improving protein production in S. lividans . Additional increases in protein production might be obtained by finding genetic targets based on a thorough understanding of the metabolic burden caused by recombinant protein production.…”
Section: Introductionmentioning
confidence: 99%